Frequency and risk factors of fractures in adolescents and young ADULTS in the population of Irkutsk - L. S. Dats (Scientific Сentre for Family Health and Human Reproduction Problems, 2016)
The aim of the study was to examine frequency and risk factors of fractures among adolescents and young adults of Irkutsk aged 14 to 24. The results of the study showed that the frequency of fractures was 23.8 %; and boys have fractures significantly more often than girls (p = 0.01). Risk factors for fractures are: male gender (OR = 1.25); body height (> 174 cm for girls (OR = 3.9), > 177 cm for males (OR = 3.5)); body weight (> 60 kg for girls (OR = 2.5), > 66 kg for boys (OR = 2.1)); tenderness to palpation of spinous processes of vertebra (OR = 3.1 for girls, and OR = 2.4 for boys); dietary calcium intake < 500 mg/day (OR = 1.5 for girls, and OR = 2.3 for boys). In addition, back pain (OR = 1.9) and joint hypermobility syndrome (Or = 1.4) were significantly more often found in girls with fractures. There was no statistically significant connection between fractures in adolescents and young adults and hypodynamia, bone mineral density, social factors (single-parent or multi-child family), and parental history of fractures.